XXI TRANSFORMATION OF MORAL VALUES IN THE CENTURY - Mukhitdin Nazarov (Western European Studies, 2025)
The transformation of moral values in the 21st century, influenced by globalization and technological development, is giving rise to new approaches to moral principles and human behavior. Among the moral criteria of the 21st century are issues concerning the true values of a person, their relationship with family, society, and life, as well as aspects such as love and kindness, justice, and the moral principles of youth. It is evident that shaping positive approaches to the moral problems of this century, as well as developing the personality of each individual and shaping their ethical norms, is of great importance. The reevaluation of morality in the 21st century has become a key task aimed at fostering individuals as active citizens and true human beings based on updated humanitarian and humanistic values.
Keywords: individual; perfection; Confucius; Jesus